Limits of Right to Freedom of Speech in the Context of Relations Between the Republic of Northern Macedonia and Bulgaria - Valcheva, Alexandra (Research Papers, 2021)
The right to freedom of expression, also called freedom of expression, has been recognized for decades in national constitutions and a number of international instruments as one of the most important values in any society. Ensuring the effective protection of fundamental human rights, including this right, has been a major goal for decades of the United Nations, the Council of Europe, the European Union and many other international organizations. They fulfill this goal by creating and implementing various instruments and mechanisms in the field of human rights, which are aimed at establishing minimum standards for the protection of the right to freedom of expression and creating conditions for its full realization by legal entities. In the policies of the European Union, the protection of the analyzed law has always been proclaimed as a priority of the European institutions. Despite this approach and the existence of a number of international and national norms for the protection of the right to free expression, there has been a worrying trend in recent years of increasing violations of this fundamental human right. An example of this trend can be found in the relations between the Republic of Bulgaria and the Republic of Northern Macedonia, in which in recent years, despite the efforts of the Bulgarian authorities, the “hate speech” is increasingly used in our southwestern neighbor.